PENGARUH EXPERIENCE TERHADAP BRAND LOYALITY M-PAYMENT SHOPEE PAY MELALUI MEDIASI EXPECTATION - Putri, Jeny Juliana; Martha, Lidya (Journal of Management Review, 2023)
This study aims to determine the effect of experience on m-payment shopeepay brand loyalty in Padang City with expectation as a mediating variable. This research is a quantitative research, namely the sampling method using accidental sampling technique with a total of 100 respondents. The data analysis technique used I this study is multiple linear refression analysis. The results of the study show that experience and expectation have a significant effect on brand loyalty m-payment shopeepay in Padang City. Experience has a significant effect on expectation. Expectation mediates the experience relationship wit the m-payment shopeepay brand loyalty in Padang City.